(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于 A.√3 B.√3/3 C.-√3 D.-√3/3(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于A.√3 B.√3/3 C.-√3 D.-√3/3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 05:09:05
(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于 A.√3 B.√3/3 C.-√3 D.-√3/3(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于A.√3 B.√3/3 C.-√3 D.-√3/3
(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于 A.√3 B.√3/3 C.-√3 D.-√3/3
(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于
A.√3 B.√3/3 C.-√3 D.-√3/3
(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于 A.√3 B.√3/3 C.-√3 D.-√3/3(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15,则b/a等于A.√3 B.√3/3 C.-√3 D.-√3/3
(asinπ/5 +bcosπ/5)/(acosπ/5 -bsinπ/5)=tan8π/15
(tanπ/5+b/a)/(1-b/atanπ/5)=tan(π/5+π/3)
(tanπ/5+b/a)/(1-b/atanπ/5)=(tanπ/5+tanπ/3)/(1-tanπ/5tanπ/3)
(tanπ/5+b/a)/(1-b/atanπ/5)=(tanπ/5+√3)/(1-√3tanπ/5)
所以b/a=√3
选A